Part III – March 1968 - Papers - Metallurgical and Electronic Properties of Pb1-xSnxTe, Pb1-xSnxSe, and Other IV-VI Alloys - Alan J. Strauss (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The Group IV elements germanium, tin, and lead form nine 1:1 compounds with the Group VI elements sulfur, selenium, and tellurium. This paper reviews the properties of the pseudobinary solid solutions formed by these compounds, including the extent of mutual solid solubility, temperature-composition phase diagrams, transport properties, deviations from stoichiometry, optical properties, and energy band structure. Particular emphasis is placed on the Pbl-xSnxTe and Pb1-xSn,Se alloys with rocksalt structure, because of current interest in these malerials for generating and detecting infrared ,radiation. ThE Group IV elements germanium, tin, and lead form nine 1:1 compounds with the Group VI elements sulfur, selenium, and tellurium. Some of the physical and electronic properties of these compounds, including their melting points1-8 and energy gaps,4'9-12 are listed in Table I. Four compounds (SnTe, PbS, PbSe, and PbTe) have the cubic rocksalt (Bl) structure. At room temperature GeTe has a rhombohedra1 structure closely related to the B1 structure, into which it is transformed at about 400°C. Four compounds (GeS, GeSe, SnS, and SnSe) have the orthorhombic B29 structure. In samples which have not been intentionally doped with impurities, the electrical conductivity is due primarily to electrons or holes produced by the ionization of donor or acceptor lattice defects associated with deviations from stoichiometry. Undoped samples of PbS, PbSe, and PbTe may be either n type or p type, depending on whether they contain excess lead or an excess of the Group VI element, respectively, but only p-type samples of the other compounds have been reported. This paper will review the properties of the pseudo-binary solid solutions formed by the nine 1:l compounds. The topics to be considered include the extent of mutual solid solubility, temperature-composition phase diagrams, transport properties, deviations from stoichiometry, optical properties, and band structure. Particular emphasis will be placed on the Pb]-xSnxTe and Pbl-xSnxSe alloys with B1 structure, which are promising materials for generating and detecting infrared radiation in the 8 to 14 µm atmospheric window and beyond. MUTUAL SOLID SOLUBILITY The extent of mutual solid solubility in the pseudo-binary systems has been investigated for fourteen of the eighteen ternary systems (in which the two terminal compounds have a common element) and for nine of the eighteen quaternary systems. In most cases, X-ray diffraction measurements made at room temperature were used to determine the structure and lattice parameter(s) of the phase(s) present in samples of various compositions prepared by freezing from the melt. In many investigations, including the extensive studies of Krebs and co-workers,13'14 the samples were annealed at elevated temperatures before X-ray measurements were made. In some cases, metallographic examination and thermal analysis have also been employed. The results for the ternary and quaternary systems are summarized in Tables II and III, respectively. (The original references should be consulted for the annealing temperatures.) The solubility of one compound in the other is at least 5 mol pct in all cases, and is often much larger. Complete solid solubility has been observed in all systems so far investigated in which the terminal compounds have the same structure, although in the PbS-PbTe system complete solubility is limited to elevated temperatures. Thus complete solid solubility occurs in five systems where both compounds have the B1 structure (SnTe-PbTe, PbS-PbSe, PbS-PbTe at temperatures above 805°C, PbSe-PbTe, and SnTe-PbSe) and in three where both compounds have the B29 structure (GeS-SnS. GeSe-~n~e-, and SnS-SnSe), as well as in two involving GeTe and a compound with B1 structure (GeTe-SnTe and GeTe-PbTe). On the basis of thermal analysis data, complete solid solubility at sufficiently high temperatures has also been reported for the GeSe-GeTe2 and SnS- pbS22 systems. This seems unlikely, however,